Using trial and error
x^4+5x^2-36 factors to (x-2)(x+2)(x^2+9)
2x^2+9x-5 factors to (x+5)(2x-1)
so
(x-2)(x+2)(x^2+9)(x+5)(2x-1)=0
set each to zero
x-2=0
x=2
x+2=0
x=-2
x^2+9=0
x^2=-9
x=3√-1
x=3i
x+5=0
x=-5
2x-1=0
2x=1
x=1/2=0.5
roots are
x=-5-2,0.5,2, and the imaginary root 3i
Answer:
I have done one question for you
hope it helps
plz Mark as brainlist
Answer: find the answer in the explanation.
Step-by-step explanation:
To use the Pythagorean theorem to prove if a triangle with the side lengths 7,14,28 is a right triangle, you will square 7 and add it to the square of 14. The square root of the sum will be equal to 28 if it is a right angle triangle. Otherwise, it is not.
(7^2 + 14^2) = 49 + 196
245
Find the square root of 245
Square root = 15.65
Since it is not 24, the triangle is not a right angle triangle.
Answer:
6 square root of 2
Step-by-step explanation:
sin theta = opposite / hypotenuse
sin 45 = 6/x
Multiply by x
x sin 45 = 6
Divide by sin 45
x sin 45/ sin 45 = 6 / sin 45
x = 6/ sin 45
x = 6/ (1/sqrt(2))
x = 6 sqrt(2)